1988
DOI: 10.1093/jn/118.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Discrimination against Ergocalciferol by the Chick is the Result of Enhanced Metabolic Clearance Rates for its Mono- and Dihydroxylated Metabolites

Abstract: Studies on the discrimination between ergocalciferol (vitamin D2) and cholecalciferol (vitamin D3) by chickens have led to conflicting conclusions. To investigate this problem in more detail, radiolabeled vitamin D and vitamin D metabolites were administered intravenously, which allowed determination of their relative plasma clearance rates. The study involved three groups of adult male chickens (five per group). Birds in group 1 were co-dosed with [3H]vitamin D2 and [3H]vitamin D3. Birds in group 2 were co-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…These authors reported higher ratios of cholecalciferol to ergocalciferol in plasma of 1.5±0.1 (pig), 1.7±0.1 (rat) and 6.3±1.2 (chick). However, when cholecalciferol and ergocalciferol were given to chicks by parenteral administration, the concentrations and clearance rates from plasma were found to be nearly identical, and the volumes of the compartment model to be similar ( hoy et al, 1988). These workers attributed the discrimination of ergocalciferol by chicks to be the result of faster plasma clearance of its metabolites, rather than enhanced removal of the parent compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors reported higher ratios of cholecalciferol to ergocalciferol in plasma of 1.5±0.1 (pig), 1.7±0.1 (rat) and 6.3±1.2 (chick). However, when cholecalciferol and ergocalciferol were given to chicks by parenteral administration, the concentrations and clearance rates from plasma were found to be nearly identical, and the volumes of the compartment model to be similar ( hoy et al, 1988). These workers attributed the discrimination of ergocalciferol by chicks to be the result of faster plasma clearance of its metabolites, rather than enhanced removal of the parent compound.…”
Section: Discussionmentioning
confidence: 99%
“…jones et al (1976b) demonstrated that the 25‐hydroxylase activity in the liver of chicks was the same towards vitamin D 2 as vitamin D 3 , and kidneys had similar activities of the 1 and 24 hydroxylases of 25‐OHD towards vitamins D 2 and D 3 . Subsequently, hoy et al (1988) demonstrated that in chicks the plasma clearance ratios of tritium labelled vitamins D 2 and D 3 , 25‐OHD 2 and 25‐OHD 3 , and 1,25 (OH) 2 D 2 and 1,25(OH) 2 D 3 were 1.5, 11 and 33 times greater for the D 2 than the D 3 derivative. Another line of evidence that some species discriminate between vitamins D 2 and D 3 is that cholecalciferol has a greater toxicity on an equivalent dose basis than ergocalciferol ( hunt et al, 1972; harrington and page , 1983).…”
Section: Introductionmentioning
confidence: 99%
“…VD 3 might have a higher affinity to both VDR and 25-hydroxylase [118,119]. Other studies have suggested a lesser affinity of VD 2 for VDBP compared to VD 3 , resulting in higher clearance and subsequently a shorter circulating half-life [120,121,122]. Recently, a meta-analysis including seven heterogeneous studies indicated that regardless of the dosage, frequency or administration (oral or intramuscular), VD 3 was more effective at raising serum 25(OH)-VD concentrations compared to VD 2 [123].…”
Section: Vd and Ckd: Current Guidelinesmentioning
confidence: 99%
“…Houghton and Vieth 41 indicated that vitamin D3 has proven to be the more potent form of vitamin D in all primate species, including humans. The use of 25(OH)D as a biomarker in nonhuman species such as birds showed vitamin D2 to be only one-tenth as effective as vitamin D3 on increasing 25(OH)D. 42 Likewise in monkeys, the concentrations of serum 25(OH)D maintained after intake of vitamin D3 were 2-3fold those maintained with comparable amounts of vitamin D2. 43 According to Houghton and Vieth, this is in part owing to diminished binding of vitamin D2 metabolites to DBP in plasma.…”
Section: Vitamin D Metabolismmentioning
confidence: 99%